Occupational risk of affective and stress-related disorders in the Danish workforce - Wieclaw, Joanna; Agerbo, Esben; Mortensen, Preben Bo; Bonde, Jens Peter (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'A population-based, nested, case–control study was carried out to quantify the risk of affective and stress-related disorders according to occupation in the entire Danish workforce. ' ' METHODS ': 'All incident hospital patients and out-patients aged 18–65 years who received a first-time-ever diagnosis of an affective disorder (ICD-10, F 30–39) or stress-related condition (ICD-10, F 40–48) in Denmark from 1 January 1995 through 31 December 1998 were identified in the Danish Psychiatric Central Research Register (N=28 971). For each case, five randomly selected referents of the same age and gender were drawn from a 5% sample of the Danish population (N=144 855). The occupation held 1 year before a person became a case was obtained from Denmark’s Integrated Database for Labour Market Research. Occupation was classified according to the Danish version of the International Standard Classification of Occupations (ICD). Relative risks (RR) and 95% confidence intervals (95% CI) for 25 occupational categories with clerical staff as the reference were calculated using a conditional logistic regression adjusted for sociodemographic covariates. ' ' RESULTS ': 'Eight occupations were associated with significantly elevated risks (RR range 1.20–1.58) among the women, while eight occupations were associated with a significantly reduced risk (RR range 0.50–0.76) among the men. The risks were highest for the teaching (RR 1.58) and health (RR 1.53) professions. Only social workers and professionals caring for mentally and physically disabled persons faced an elevated risk irrespective of gender (women RR 1.72, 95% CI 1.38–2.16; men RR 2.09, 95% CI 1.38–3.15). ' ' CONCLUSIONS ': 'Major depression and stress-related psychiatric disorders are related to occupation. Risk profiles vary strongly according to gender.
Keywords: affective disorder; Denmark; gender; mental disorder; occupational code; occupational risk; profession; relative risk; socioeconomic status; stress-related disorder; workforce